Mucopolysaccharidosis Type I in the Russian Federation and Other Republics of the Former Soviet Union: Molecular Genetic Analysis and Epidemiology - Voskoboeva, E. Yu; Bookina, T. M.; Semyachkina, A. N.; Mikhaylova, S. V.; Vashakmadze, N. D.; Baydakova, G. V.; Zakharova, E. Yu; Kutsev, S. I. (Frontiers in Molecular Biosciences, 2022)
The mutations in IDUA gene cause a deficiency of the lysosomal enzyme alpha-L-iduronidase (IDUA) which leads to a rare disease known as mucopolysaccharidosis type I (MPS I). For today more than 220 pathogenic variant have been described in the IDUA gene, but due to the low incidence of the disease, little is known about the distribution of mutations in different population and ethnic groups. This article presents the results of the long-term molecular-genetic study of 205 MPS I patients from the Russian Federation (RF) and some other republics of the Former Soviet Union. 172 Russian (Slavic) patients, 9 tatars and 24 patients from other republic of the Former Soviet Union were fully genotyped. 75 different pathogenic variant in IDUA gene were detected. The common variant p.Gln70Term was prevalent mutant allele among Russian patients and tatars (61,9% and 50%, respectively). The second common variant p.Trp402Term along with the described mutation p.Gln380Term were account for 5,8 % and 5,5%, respectively, in Russian patients. The p.Gln70Term, p.Trp402Term and p.Gln380Term were found rarely or not found at all in patients from other population groups. The pathogenic variant p.Gln63Term was major allele in patients of Turkic origin (Altaians, Uzbeks, and Kyrgyz). Some tendencies have identified towards the accumulation of certain pathogenic alleles among patients of different ethnic groups. The obtained data provide prerequisites for identifying the molecular genetic basis of MPS I in certain populations. This is important for understanding of the molecular origin of the disease, predicting its risk development, and creating optimal diagnostic tools in specific regions and ethnic groups.